how does the derivative of

-1/ (x - 1)^2

=

2/ (x - 1)^3

seems simple..but i get x in the numerator :(

Printable View

- Apr 15th 2010, 06:09 AMcalculus0simple quotient rule
how does the derivative of

-1/ (x - 1)^2

=

2/ (x - 1)^3

seems simple..but i get x in the numerator :( - Apr 15th 2010, 06:27 AMTWiX
$\displaystyle \frac{-1}{(x-1)^2}=-(x-1)^{-2}$

It should be easy now

Right? :D - Apr 15th 2010, 06:32 AMcalculus0
thank you but do you know how do do it with quotient rule? my teacher emphasizes this.

- Apr 15th 2010, 06:41 AMe^(i*pi)
$\displaystyle u = -1 \: \rightarrow \: u' = 0$

$\displaystyle v = (x-1)^2 \: \rightarrow \: v' = 2(x-1)$

Quotient Rule $\displaystyle y' = \frac{u'v - v'u}{v^2}$

In this case we can get rid of $\displaystyle u'v$ because it equals 0.

$\displaystyle y' = -\frac{v'u}{v^2}$. Remember your signs and factors - Apr 15th 2010, 07:26 AMcalculus0
im so horrible at this..

after 1/2 the equation disappears multiplying by zero i get:

2

-----------

(x - 1)

which is not equal to the solution

2

------------

(x - 1)^3 - Apr 15th 2010, 07:58 AMe^(i*pi)
- Apr 15th 2010, 08:20 AMcalculus0
think i got it...e^(i*pi)

thanks so much